Franchising-Modern Form of Business for Small and Medium sized Enterprises - Jozef Orgonáš (International Journal of Small and Medium Enterprises and Business Sustainability, 2017)
Franchising is a specific form of business, which began with a solid development in the 50th of last century, whereby the noticeable dynamics gained at the end of last two decades of 20th century. Its specific substance wins by offering of attractive possibilities for small and medium sized enterprises, in particular by effectiveness and lifetime stability in first five years of business activities and its positive vision for survival in the period of crisis and turbulent time. The successfulness of entrepreneurship by franchising form is one of the safety forms of entrepreneurial activity. It offers anyway the rational format with clearly divided tasks, which is the base of dynamical and effective system, at which its compactness, integrity and reliability is the precondition of surviving and achieving of success, for both parties ̶ the franchisor and for franchisee, as well. Franchising is model for small and medium sized enterprises and family owned business, as well, which works well if both sides become integrated with it.